PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA SHOWROOM PERINTIS MOTOR (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study aims to examine the effect of service quality on customer satisfaction in the Showroom Perintis Motor. Research this use approach quantitative and design selected research by author is Causal Research. Population that will researched is consumer Showroom perintis motor who don't is known the amount, so for calculate amount minimum sample needed use formula calculation of Hair et al, whose the number of samples as big as 115 respondents. Technique data collection is used in research this is questionnaire distribution, observation and literature study. The results research obtained show that the independent variable (service quality) has a positive influence on the dependent variable (customer satisfaction). Consumer feel satisfied because of employee Showroom Perintis Motor do service whose done when this, as well able to give information with obviously that turns out influence level satisfaction consumers. The result research aforesaid certainly there are suitability against several result analysis whose done by research-research foregone.